2015
DOI: 10.1186/s12905-015-0166-5
|View full text |Cite
|
Sign up to set email alerts
|

Multiplicative disadvantage of being an unmarried and inadequately insured woman living in poverty with colon cancer: historical cohort exploration in California

Abstract: BackgroundMany Americans diagnosed with colon cancer do not receive indicated chemotherapy. Certain unmarried women may be particularly disadvantaged. A 3-way interaction of the multiplicative disadvantages of being an unmarried and inadequately insured woman living in poverty was explored.MethodsCalifornia registry data were analyzed for 2,319 women diagnosed with stage II to IV colon cancer between 1996 and 2000 and followed until 2014. Socioeconomic data from the 2000 census classified neighborhoods as high… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
18
0

Year Published

2016
2016
2021
2021

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 16 publications
(19 citation statements)
references
References 36 publications
1
18
0
Order By: Relevance
“…Pattern of death was examined in women of single marital status for cervical cancer (Table S3, 32,628 women with cervical cancer remained for analysis. All variables were statistically similar between the 2 groups (all, P 9 0.10).…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Pattern of death was examined in women of single marital status for cervical cancer (Table S3, 32,628 women with cervical cancer remained for analysis. All variables were statistically similar between the 2 groups (all, P 9 0.10).…”
Section: Resultsmentioning
confidence: 99%
“…A possible explanation for increased infectious mortality despite early stage of diagnosis for single women is underuse of the health care system and the aforementioned effect of inadequate social support on mental wellbeing, immune function, and overall health. 31,32 Strengths of this study include that this is a populationbased study with a large-scale sample size and adjustment for patient clinical demographic characteristics by propensity score matching analysis. The quality of our analysis in this study was greatly enhanced by propensity score matching, which has been argued to be a powerful means of accounting for baseline confounding and selection biases.…”
Section: Discussionmentioning
confidence: 99%
“…As with other American women, marriage is positively associated with adequate health insurance coverage among Chinese American women (Levitz et al 2015;Tan 2009). Marriage and/or health insurance have also been significantly associated with a range of behaviors among Chinese Americans that, together, could bode for better colon cancer outcomes.…”
mentioning
confidence: 99%
“…Research in the same context as the present study has shown that gender and marital status interact with health insurance adequacy which influences cancer survival. For example, among women with colon cancer, poverty and inadequate health insurance coverage were more prevalent among unmarried women (Levitz et al 2015). Among those living near or below the poverty line with colon cancer, private health insurance was associated with survival among married women, but not men.…”
mentioning
confidence: 99%
“…Most people studied received such a colectomy (93% to 98%). Preliminary analyses suggested that the uninsured may be at grave risk of its nonreceipt and that women may be at greater risk than men (Campbell et al, 2016;Levitz et al, 2015). This secondary analysis explored that novel gender by health insurance hypothesis.…”
Section: Introductionmentioning
confidence: 99%